Pengaruh Digital Marketing pada Pemilihan Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan - Suryana Hendrawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of digital marketing consisting of websites, search engine optimization, digital advertising, affiliate and partnership marketing, online public relations, social networking, email marketing, consumer relationship management on the election decision of the Ahmad Dahlan University Faculty of Economics and Business (FEB). UAD). This study uses a quantitative approach. The sample used in this study was obtained by probability sampling method and simple random sampling was used on active students of FEB UAD with a target sample size of at least 100 people. This study uses primary data as a source of data obtained by distributing questionnaires using a Likert scale by making a list of statements to be filled in by respondents to obtain data in the form of data to be analyzed and tested using partial and simultaneous multiple regression analysis. using the F test and T test. The results of this study indicate that togetherdigital marketing can influence the selection of FEB UAD, and what can most influence is digital advertising (pay per click) and how companies can manage relationships with their customers.